Strategi Pembentukan Karakter Tanggung Jawab di Panti Asuhan Amanah V Suku Canduang Kab. Agam - Murniati, Murniati; Aprison, Wedra (Al-DYAS, 2023)
The case in this research is to explain: What is the strategy for creating a responsible personality at the Amanah V Kaum Canduang Orphanage, Agam Regency. The aim of this research is: To define strategies for creating a responsible personality at the Amanah V Kaum Canduang Orphanage, Kab. Religion. The aim of this research is to identify strategies for forming the character of responsibility in the Amanah V orphanage for the Canduang community in Kab. Agam, Supporter and Advocate of Personality Creation at the Kaum V Orphanage, Canduang Regency, Agam. The procedures used by the author in this research are qualitative descriptive research procedures. The important informants in this research are guards or caretakers as well as guiding children in orphanages. Procedures for collecting information through monitoring, questions and answers and deeds. The procedure for analyzing information uses 3 steps, namely descriptive (analysis), information reduction, and information understanding. To test the validity of the information, the triangulation method is used, namely basic principles, procedures and philosophy. The results of this research prove that developing a responsible personality is very important for orphans. (1) The strategy for creating a responsible personality is making the bed every morning, cleaning the dishes after eating, practicing diligently, cleaning one's own clothes, and praying together at the prayer room near the orphanage. upbringing. (2) The aspect that supports and advocates strategies for creating a responsible personality has been attached to the family or community of origin before entering the institution, and is still carried over when living in the institution, and the emergence of a heavy-handed character and bored impulses that originate from the child. self. The support of guards, teachers, caretakers, areas and associations in the orphanage is very supportive for creating a responsible personality.